Synergistic effects of trace ZrC/Zr on the mechanical properties and microstructure of tungsten as plasma facing materials. (May 2019) - Zhang, T.; Wang, Y.K.; Xie, Z.M.; Liu, C.S.; Fang, Q.F.
Highlights: W, W–0.5wt%ZrC and W–2.0wt%Zr–0.5wt%ZrC alloys are fabricated using vacuum hot pressure method. The synergistic addition of Zr/ZrC can increase the sinter ability of W. The trace Zr/ZrC addition can further refine the tungsten grain size compared with only ZrC addition. The synergistic addition of Zr/ZrC can significantly enhance the ductility/plasticity and strength of tungsten. The results of microstructure and mechanical properties of SPSed specimen and VHPed specimen have been compared. Abstract: Pure W, and W–0.5wt%ZrC (WZC) and W–2.0wt%Zr–0.5wt%ZrC (WZZC) alloys are fabricated using vacuum hot pressure (VHP) method to investigate the effects of trace ZrC or Zr/ZrC on the mechanical properties and microstructure of tungsten. It was found that from W to WZC and to WZZC, the average grain size was refined from 6.2 µm of W to 5.8 μm of WZC and finally to 4.8 um for WZZC and relative density increase continually from 97.0% to 98.0% and to 98.5%. The tensile tests indicated that ZrC or ZrC/Zr significantly increases the strength and ductility/plasticity. The comparison of VHPed and spark plasma sintered (SPSed) specimen are made. The microstructure analysis indicate that the W–Zr–O and/or Zr–C–O particles resulting from the reaction of Zr or ZrC with free O pin grain boundaries (GBs) of tungsten and inhibits the migration of GBs, and then refining the grain size. The synergistic effects of the decrease of free O impurity and nano-sized ZrC dispersion strengthening strengthen GBs and improve the mechanical properties.